2003
DOI: 10.1046/j.1600-9657.2003.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bioactive glass, mineral trioxide aggregate, ferric sulfate, and formocresol as pulpotomy agents in rat molar

Abstract: Bioactive glass (BAG) is often used as a filler material for repair of dental bone defects. Although there is evidence of osteogenic potential of this material, it is not clear yet whether the material exhibits potential for dentinogenesis. Hence, the aim of the present study was to evaluate BAG as a pulpotomy agent and to compare it with three commercially available pulpotomy agents such as formocresol (FC), ferric sulfate (FS), and mineral trioxide aggregate (MTA). Pulpotomies were performed in 80 maxillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 10 publications
(8 reference statements)
4
47
1
10
Order By: Relevance
“…In the literature there are a limited number of animal studies on pulp capping in which MTA has been compared with Ca(OH) 2 in monkeys (Pitt Ford et al 1996), dogs (Tziafas et al 2002, Asgary et al 2006) and rats (Salako et al 2003). These studies consistently demonstrated more hard tissue bridge formation and less inflammation in the MTA group compared with the Ca(OH) 2 control over a 2-5 month period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are a limited number of animal studies on pulp capping in which MTA has been compared with Ca(OH) 2 in monkeys (Pitt Ford et al 1996), dogs (Tziafas et al 2002, Asgary et al 2006) and rats (Salako et al 2003). These studies consistently demonstrated more hard tissue bridge formation and less inflammation in the MTA group compared with the Ca(OH) 2 control over a 2-5 month period.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have also been made to use it as a root canal filling material in dogs (Holland et al 1999b). Dentine bridge-like hard tissue was consistently observed when MTA was used as a pulp capping agent in monkeys (Pitt Ford et al 1996), dogs (Tziafas et al 2002, Asgary et al 2006 and rats (Salako et al 2003). It is essential to test the pulp healing ability of MTA on human teeth before its routine clinical application (ISO 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The superior sealing ability of MTA over conventional retrograde filling materials, such as amalgam, IRM, and Super EBA, has been demonstrated in numerous microleakage tests using dye, fluid, bacteria, and endotoxin infiltration techniques (5-10). Its excellent biocompatibility has been evidenced in several favorable biologic processes induced by MTA, namely, minimal toxicity and pulpal irritation, mild periapical inflammation, nonmutagenicity, cell adherence and growth, increased levels of alkaline phosphatase and osteocalcin, interleukin production (IL-6, IL-8), periodontal ligament attachment, cementum growth, and dentinal bridge formation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).Studies on MTA have mainly examined its various biologic properties, but little or no attention has been paid to the fundamental physicochemical interaction between MTA and the oral environment that instigates those biologic responses. The purpose of this study was to elucidate the nature of this interaction, specifically to characterize the interaction of MTA with (a) a synthetic tissue fluid (STF) and (b) endodontically prepared root canal walls in extracted human teeth.…”
mentioning
confidence: 99%
“…Being originally developed as a surgical root end filling material, MTA has been successfully used in several clinical applications such as pulp capping [5] pulpotomy [6] perforation repair [7] treatment of traumatized teeth with immature apices [8] and for treatment of root resorptions [9].…”
Section: Introductionmentioning
confidence: 99%